Co-precipitation synthesis of Co2+xFe2+1-xFe2O4nanoparticles: Structural characterization and magnetic properties - Soleimani, H. (American Institute of Physics Inc., 2014)
Cobalt ferrite is known as a promising magnetic material for various applications. This metal-ceramic composite (Cox2+Fe1-x2+Fe2O4) was synthesized via co-precipitation route, by varying the Co/Fe ratios (Co/Fe = 0.3, 0.2, and 0). The structures and magnetic properties of nano-composites were analyzed by XRD and VSM. As deduced from the XRD line broadening, the average crystallite size of the samples was found to be in the range of 13.0-15.0 nm and contain fcc structure with smaller lattice constant as the Co/Fe ratios increases. FESEM and TEM images revealed the morphology of the samples, which consist of irregular shapes of diameter in the range of 9.0-15.0 nm. Magnetic properties measurement shows that sample S11 with the highest Co/Fe ratio has the highest value of saturation magnetization (Ms) of 65.23 emu/g. On the other hand, increase in the concentration of cobalt ions improves the remanence magnetization (Mr) and coercivity (Hc) of the same sample to 12.18 emu/g and 238.92 Oe, respectively. It is demonstrated that the higher substitution ratio of cobalt in Cox2+Fe1-x2+Fe2O4 has successfully improve the magnetic properties of the samples. Â© 2014 AIP Publishing LLC.